Is Mindful Reflective Practice the way forward to reduce medication errors?. (12th April 2013) - Pezzolesi, Cinzia; Ghaleb, Maisoon; Kostrzewski, Andrzej; Dhillon, Soraya
Abstract: Background: Medication errors can seriously affect patients and healthcare professionals. In over 60% of cases, medication errors are associated with one or more contributory; individual factors including staff being forgetful, stressed, tired or engaged in multiple tasks simultaneously, often alongside being distracted or interrupted. Routinised hospital practice can lead professionals to work in a state of mindlessness, where it is easy to be unaware of how both body and mind are functioning. Objective: Mindfulness, defined as moment‐to‐moment awareness of the everyday experience, could represent a useful strategy to improve reflection in pharmacy practice. The importance of reflection to reduce diagnostic errors in medicine has been supported in the literature; however, in pharmaceutical care, reflection has also only been discussed to a limited extent. There is expanding evidence on the effectiveness of mindfulness in the treatment of many mental and physical health problems in the general population, as well as its role in enhancing decision making, empathy and reducing burnout or fatigue in medical staff. Considering the benefits of mindfulness, the authors suggest that healthcare professionals should be encouraged to develop their practice of mindfulness. This would not only be beneficial in relieving stress, increasing attention levels and awareness, but it is believed that the integration of mindfulness and reflective practice in a 'Mindful Reflective Practice' could minimise some of the individual factors that lead to medication errors. Conclusions: Mindfulness Reflective Practice could therefore represent an important element in pre‐registration education and continual professional development for pharmacists and other healthcare professionals.